It works; it doesn't; it can, but that depends...: 50 years of controversy over the macroeconomic impact of development aid - Mark McGillivray; Simon Feeny; Niels Hermes; Robert Lensink (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper surveys 50 years of empirical research on the macroeconomic impact of aid, looking mainly at studies examining the link between aid and growth. It argues that studies dating until the late 1990s produced either contradictory or inconclusive results. Aid either worked, or it didn't, according to this research. The paper then highlights a major shift in the literature that coincided with the release of the World Bank's Assessing Aid: What Works, What Doesn't and Why. Practically all research published since that report agrees with its general finding that aid works, to the extent that in its absence growth would be lower. One controversy may therefore have been settled. Yet, we show, the report has set-off an intense debate over the context in which aid works. That debate centres on whether the effectiveness of these inflows depends on the policy regime of recipient countries. Some possible avenues through which the heat might be taken out of this debate are considered. – aid ; savings ; investment ; growth ; econometrics ; policy
Keywords: F35; C23; O11; O47; E21; E22; 330; Entwicklungshilfe; Theorie; Entwicklungsländer; Makroökonomischer Einfluss